THE EFFECT OF SOME FRESH WATER ALGEA EXTRACTS IN THE INHIBITION OF THE GROWTH OF SOME MICROORGANISIM THAT CAUSE FOOD SPOILAGE - Karm, I. F. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was carried out to isolate, identified and study two types of Iraqi fresh water algae Scenedesmus sp. and Oscellatoria sp also determine some of their active compounds that play an important role as antioxidants and antimicrobial againsts some bacteria. Three types of bacteria Salmonella sp, Escherichia coli and Staphylococcus sp that cause spoilage for food were tested. Antimicrobial activity of ethanolic extracts for both algae were examined toward tested bacteria. Four treatments were prepared which were [S.Ex(T1) ,O.Ex(T2), S.Ex: Of*(T3), 1:1 O.Ex: Of*(T4) 1:1],and (C) as control treatment with the antibiotic only (Oflaxacin). Disk diffusion method was used to test the antibacterial activity. Some active compounds indicate and high performance liquid chromatography (HPLC) technique used to determine some of them . Both algae contain some active ingredients that consider to be the reason for their ability as antimicrobials. The results of this study showed that the highest inhibition zones were in the treatments T3 and T4 compared to control treatment that means the synergistic activity for both antibiotic and the algae extract as alternative sources gave a better result for health and food protection.